Changes in the Financial Condition of Families in Hungary between 2000 and 2019 - Szentesi, Ibolya; Csizmásné Tóth, Judit; Gáspár, Andrea; Horváthné Kökény, Annamária (International Journal of Engineering and Management Sciences, 2020)
The financial condition of families living on wages is function of many factors. It is determined, among other things, by the development of wages, social benefits, tax rates and the amount of allowances that can be granted. The part of the tax system that affects the largest segment of individuals changes every year, and even during the year, reducing predictability. In recent years, discussions over the taxes have shown that the rate of personal income tax cannot be evaluated separately from the social security contribution rate. Gross average earnings - on the grounds of raising the minimum wage and the guaranteed minimum wage - have more than four-times in nearly 20 years. However the rate of growth is higher in the average net earnings due to changes in the tax system. Compulsory determined wages increased to almost six-times over the years under investigated. But in 20 years, how much has the income situation of an average family living on a salary become more favourable or more unfavourable? In our study we are looking for an answer to how the increase in the minimum wage and the changes in the law how to have affected the livelihood.